Comparison ondansetron and domperidon as antiemetic for gastroenteritis in children: a review - Siregar, Mardiana; Wiedyaningsih, Chairun; Mutiara, Rina (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Gastroenteritis (GE) is the leading cause of vomiting in children. It is the main reason children admitted into emergency departments (EDs). Vomiting can cause fluid loss therefore oral rehydration solution (ORT) is recommended as supportive care for mild to moderate dehydration. Antiemetic therapy for GE is not fully recommended by any management guidelines. However, in some studies, antiemetics including ondansetron and domperidone are used in vomiting-related GE. This review aimed to compare ondansetron and domperidone for the treatment of GE in children. The article search was performed to identify relevant publications using PubMed database PubMed. PRISMA flow diagram was used as protocol during the article screening process. Eight